Pupuan Natural Potential Learning Video Based on Inquiry Learning for Grade IV Elementary School Science Content - Ni Luh Gede Agustin Marheni; I Gusti Agung Ayu Wulandari; Komang Sujendra Diputra (Jurnal Edutech Undiksha, 2025)
The integration of innovative learning media in the learning process, especially in elementary schools, plays a strategic role in enhancing students’ learning motivation, which ultimately impacts their learning outcomes. However, in practice, learning activities that are not supported by appropriate media tend to be less engaging. The learning model applied also influences students’ motivation, indicating that both learning models and media play a crucial role in improving motivation. This study aimed to develop a Pupuan natural potential learning video based on inquiry learning for Grade IV IPAS content on the topic 'My Region and Its Natural Resources.' This research employed a development design using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Data collection methods included questionnaires and tests, with trial subjects consisting of material experts, design experts, media experts, and Grade IV students. The data were analyzed using descriptive quantitative and inferential statistics. The results showed that validation by material experts reached 91.07% (very good), design experts 92.5% (very good), media experts 93.3% (very good), individual trials 97% (very good), and small group trials 90.02% (very good). Effectiveness testing yielded an average post-test score of 86.33, which exceeded the minimum mastery criterion (70). These findings indicate that the Pupuan natural potential learning video based on inquiry learning is effective for use in elementary IPAS learning.